Efficiency and equality in a simple model of efficient unemployment insurance. - Atkeson, Andrew; Lucas, Robert E. (Journal of Economic Theory, 1995)
The writers describe the efficient allocation of consumption and work effort in an economy in which workers face idiosyncratic employment risk and where full insurance is prevented by issues of moral hazard. They present a model of the long-run consequences of efficient unemployment insurance for the distribution of welfare and consumption for these workers, define the efficiency problem, and establish the connection between the original efficiency problem and a one-on-one principal-agent problem. They consider the solution to the one-on-one principal-agent problem, examine the Markov process of entitlements generated by the solution to this problem, and demonstrate that the steady-state level of resource use is a continuous, increasing function of the interest rate, thereby establishing the existence of a market clearing interest rate.